Studi Literatur Terkini Model Generator Heffron-Phillips - Prasetiyo, Ari Puji (Sekolah Tinggi Teknologi Ronggolawe Cepu, 2025)
This literature review examines the application and development of the Heffron–Phillips model across eight recent scholarly articles focused on the dynamic stability of electric power systems. The Heffron–Phillips model is widely utilized in SMIB configurations to linearly represent the dynamics of synchronous generators and serves as a foundation for designing and optimizing various controllers, such as PSS, supple-mentary damping controllers, and AVR. Several studies extend or modify this model to incorporate modern components, including IPFC, grid-following inverters, and machine learning-based algorithms. The review finds that the model remains highly relevant for small-signal analysis, adaptive controller design, and algorithm performance validation. However, its limitations in addressing ultra-low frequency oscillations and the nonlinear dynamics of renewable-based systems highlight the need for more advanced or frequency-domain models. Overall, the Heffron–Phillips model continues to serve as a critical foundation in power system modeling, though it must be adapted to remain effective in the increasingly complex and dynamic architecture of modern power networks.